Experimental investigation on effect of additional reservoir onto conventional impedance pumping system - Lee, Vincent; Abakr, Y.; Woo, K.; Al-Atabi, M. (2011)
Impedance pumping is defined as a valveless pumping mechanism, where an elastic tube is joined with a tube of different impedance, a periodic asymmetrical compression on part of the elastic tube will produce a unidirectional flow. Numerical and experimental studies had been conducted in the past in the field of impedance pumping, but no experimental work was found to exploit the principle of multi-stage impedance pumping for fluid transportation. This piece of work describes the investigation of the effect of additional reservoir onto the existing conventional impedance pumping system. Pressure head increment is proven to be viable in this experiment. A pressure head increment of 240 Pa is obtained in the two reservoirs single actuator system, 180 Pa in the three reservoir single actuator, and 480 Pa in the three reservoirs two actuator system. Flow rate of 5 mL/s, 6 mL/s and 8 mL/s is obtained for the two reservoirs single actuator, three reservoirs single actuator and three reservoirs two actuator system respectively. Results presented are of great significant and showed an increment of 100% in the pressure head and 60% in the flow rate in the three reservoirs system as compared to the conventional system. © School of Engineering, Taylor's University.